Coping with asthma in racially and ethnically diverse urban children: The role of emotional problems in disease control. Issue 2 (3rd April 2017) - Rodríguez, Erin M.; Kumar, Harsha; Draeger, Annie; Sánchez-Johnsen, Lisa
ABSTRACT: This study examined cross-sectional associations among coping, mental health, and asthma outcomes in racially/ethnically diverse urban children. Children ( N  = 42; 65% female) ages 9 to 17 ( M  = 11.9) years old and their parents reported on the child's coping, emotional and conduct problems, asthma control, and school missed due to asthma. Higher child and parent reported secondary control coping was correlated with fewer mental health problems and better child reported asthma control. Child reported emotional problems partially accounted for associations between child and parent reported secondary control coping and child reported asthma control. Secondary control coping may improve asthma by reducing emotional difficulties.